دور مناخ التمكين النفسي في تفعيل حالة الولاء التنظيمي للأفراد العاملين في المنظمة (دراسة تحليلية لمنظمات القطاع العام السياحي في محافظتي دمشق واللاذقية) - عواد, يونس; رجب, حيدرة (Latakia University Journal - Economic and Legal Sciences Series, 2014)
هدفت هذه الدراسة إلى تسليط الضوء بشكل أساسي على دور مناخ التمكين النفسي (بأبعاده الأربعة) وأهميته في تفعيل حالة الولاء التنظيمي للعاملين في منظمات القطاع العام الخدمي السياحي محل الدراسة، ومن أجل ذلك قام الباحث بتصميم قوائم استبانة خاصة بهذا الغرض شملت 210 عامل في منظمات القطاع العام الخدمي السياحي في محافظتي دمشق واللاذقية تم توزيعها بشكل عشوائي وتمثلت النتائج على النحو الآتي: انخفاض معدل مناخ التمكين النفسي (بأبعاده الأربعة) في منظمات القطاع العام السياحي للعاملين محل الدراسة. انخفاض معدل الولاء التنظيمي في منظمات القطاع العام السياحي للعاملين محل الدراسة. وجود علاقة إيجابية ذات دلالة معنوية بين أبعاد مناخ التمكين النفسي (المعنى – الاستقلالية – الكفاءة- الأثر) والولاء التنظيمي كافة. وفي ضوء ما تم التوصل إليه من نتائج توصي الدراسة بضرورة تفعيل الدور الاستراتيجي لإدارات الموارد البشرية وأخذ مواقعها المتقدمة على خارطة هيراركية الاستراتيجية على المستوى التنظيمي حتى تستطيع تنسيق ومكاملة وظائفها كافة وتوجيهها بالاتجاه الذي يدعم مناخ التمكين النفسي للعاملين وذلك من خلال إرساء ثقافة تنظيمية داعمة للإبداع معززة بتصميم هياكل عضوية مرنة تسمح بممارسة تلك الوظائف والممارسات من منظور سلوكي استراتيجي. This research aims basically to highlight the role and importance of climate psychological empowerment (by its four dimensions) in the activation of organizational loyalty status of employees in Tourist Public Service Sector organizations (TPSS) at issue. For that reason, the researcher has randomly distributed copies of the questionnaire for 210 employees working in (TPSS). The results obtained are as follows: There is a low rate of the climate psychological empowerment (by its four dimensions) in Tourist Public Service Sector organizations for the personnel concerned. There is a low rate of organizational loyalty in Tourist Public Service Sector organizations for the personnel concerned. There is a significant positive relationship between all the dimensions of the climate of psychological empowerment (Meaning, Autonomy, competence, Impact) and organizational loyalty. In the light of the results obtained, this study recommends that attention be given to activating the strategic role of human resources management, making them hold their advanced positions in order to be able to coordinate and integrate all their functions and then direct these functions towards supporting the climate of psychological empowerment for personnel through the establishment of an organizational culture supportive of creativity, enhanced by a flexible organic structure design allowing to practice these functions from a strategic behavioral perspective.